Efektivitas Mobile Health terhadap Kepatuhan Minum Obat Pasien Tuberkulosis - Lie Liana Fuadiati; Tintin Sukartini; Makhfudli Makhfudli (Journal of Telenursing (JOTING), 2023)
This study aims to review the effectiveness of mobile health on medication adherence in tuberculosis patients. The method used is the Preferred Reporting Items for Systemic Review and Meta-Analysis (PRISMA) Guidelines with an online literature search strategy using the google chrome search engine CINAHL, PubMed, SAGE, Science Direct, and Scopus. The year of the literature source was taken from 2016 to 2021. From the articles searched, 7 articles were obtained and reviewed. The results of this study indicate that of the 7 articles reviewed, 5 articles indicate the necessary role of technology, namely the application of drug-taking supervisors to improve drug adherence for tuberculosis patients. The 2 articles stated that reminders to take medication via SMS were not considered optimal. In conclusion, the role of drug monitoring application technology is effective in increasing drug adherence for tuberculosis patients, while reminders to take medication via SMS are considered less effective. Keywords: Mobile Health, Medicine Adherence, Telemedicine, Tuberculosis Patient